Cytotoxic effect of red 40 food dye in Artemia salina nauplii - Mostacero-León , José (2020)
Recent research supports the fact that many of the dye-type food additives used in the food industry, far from satisfying the organoleptic requirements of the population; greatly reduce the health of those who consume it; such is the case of red 40 widely used in Peru. Based on what has been described, this research focused on determining the cytotoxic effect of red food dye 40 in Artemia salina nauplii. For this, a nauplos incubation system was installed, to then be exposed to different concentrations of the dye under study, forming the treatments: T0: 0.00 (mg / L), T1: 3.125 mg / L, T2: 15.625 mg / L and T3: 31.25 mg / L and finally measure their morta- lity after 48 hours. The results showed that T0 had a 0% lethality, T1 had a 60% lethality, T2 a 100% lethality and T3 a 100% lethality. It is concluded that the red food dye 40 presented a cytotoxic effect and hyperactivity in locomotion in nauplii of Artemia salina, with an LC 50 of 2.6.